Kepemimpinan kolektif dalam pengembangan budaya organisasi: literature review study - Raharjo, Santosa Budi; Gunarsih, Tri; Wening, Nur (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
Leadership in a more specific scope becomes a valuable capital in managing the organization. The research method used is a Systematic Literature review. Based on the results of article collection on the classification of sources, themes, and years of publication of articles, 35 articles were obtained that met the article classification. The results show that collective leadership is a collaborative and mutually beneficial leadership process, which allows all elements of an institution to take part in building a certainty that accommodates common goals. Leadership collectivity is the behavior and nature of leaders who involve all staff, to be able to form an organizational culture to be able to work by their respective authorities and duties through a mutually arranged organizational culture, as well as collaborate and be responsible with a collective leadership structure.